Implementasi Pendidikan Karakter Berbasis Pendidikan Agama di Sekolah - Miftahul Ilmi; Amzah Selle; Munawir (IAIN PAREPARE, 2021)
This article discusses the implementation of Islamic character education in the school. The purpose of this study was to describe the planning, implementation, and impact of the implementation of Islamic character education. This research is a qualitative research with the instruments used in this study, namely observation guidelines, interview guidelines and researchers as key instruments. The informants interviewed in this study were school principals, Islamic religious education teachers and students. The results showed that the planning of character education based on religious education was carried out by making plans in the form of a lesson plan implementation plan. The implementation of character education is carried out by integrating character ivalues ​​into Islamic religious education materials, especially with regard to moral material that is applied using the inquiry method. Implementation of character education in learning Islamic religious education has an impact on improving the quality of learning. Implementation of character education in learning Islamic religious education has an impact on improving the quality of learning. Implementation of character education in learning Islamic religious education has an impact on improving the iquality of learning that is more fun, motivating, inspiring, and meaningful. In addition, students are inspired to live up to character values ​​such as caring, politeness, and honesty to be applied in ieveryday interactions.